3D Graphite–Polymer Flexible Strain Sensors with Ultrasensitivity and Durability for Real‐Time Human Vital Sign Monitoring and Musical Instrument Education. Issue 6 (20th April 2017) - Li, Weigu; Guo, Jianhe; Fan, Donglei
Abstract : The design and fabrication of various types of flexible, portable, and foldable devices have received immense interest owing to the remarkable potential in impacting peoples' lives including real‐time health monitoring, point‐of‐care diagnosis, and athletic training. In this work, the authors present 3D graphite as the key sensing element of polymer composite strain sensors that offers ultrahigh sensitivity and durability in the detection of fine motions. The graphite–polymer sensors in this work provide high bending sensitivities that are reproducible within 3% signal shift after 11 000 bending cycles and exhibit gauge factors of 100 and 52 at tensile strains of 80% and 100%, respectively. The sensing mechanism is modeled, and correlated with experimental studies. The high strain sensitivity compared to graphene based devices is analyzed and understood with respect to levels of defect in materials. Such graphite–polymer sensors are able to detect fine features of human pulses, respiration rates, and throat vibration in real time and are also applied in the detection of posture correctness of musical instrument learners for the first time. Abstract : The work reports an ultrasensitive and durable flexible strain sensor based on graphite, its characteristics and applications in both human vital sign monitoring as well as musical instrument education, i.e., for determining posture correctness of violin learners. The high strain sensitivity is analyzed and understood by the level of defects in materials, and the enhancement to piezoresistivity.